An Abbreviated Screening Instrument for Autism Spectrum Disorders. Issue 2 (26th July 2012) - Smith, Nicola J.; Sheldrick, R. Christopher; Perrin, Ellen C.
Abstract The reliability and validity of the Parent's Observations of Social Interactions (POSI), a new, seven‐item screening instrument for autism spectrum disorders (ASD), is examined in two substudies. In Study 1, parents of 217 children (18–48 months) evaluated at a developmental clinic completed intake questionnaires that included the POSI and the Modified Checklist for Autism in Toddlers (M‐CHAT) checklist. POSI and M‐CHAT scores were compared to clinical evaluation results to assess reliability and validity. In Study 2, parents of 232 children (16–36 months) from both primary care and subspecialty settings completed the POSI, the M‐CHAT, and a report of their child's diagnoses. POSI and M‐CHAT scores were compared to reported diagnoses to assess reliability and validity. In both studies, the POSI demonstrated adequate internal reliability (Cronbach α = 0.83 and 0.86, respectively). In Study 1, POSI sensitivity (89%) was higher than that for the M‐CHAT (71%; p < .05); specificities were not significantly different (POSI: 54%, M‐CHAT: 62%). In Study 2, sensitivity (83%) compared favorably to that for the M‐CHAT (50%), although specificity was lower (75 vs. 84%). Despite its brevity, the POSI demonstrated good internal reliability and comparable sensitivity/specificity to the M‐CHAT checklist in two independent populations. If results are reproduced in larger, more diverse samples, the POSI may provide an efficient method for ASD screening in young children.